Informed Molecular Design of Conjugated Oligoelectrolytes To Increase Cell Affinity and Antimicrobial Activity. Issue 27 (30th May 2018) - Zhou, Cheng; Chia, Geraldine W. N.; Ho, James C. S.; Seviour, Thomas; Sailov, Talgat; Liedberg, Bo; Kjelleberg, Staffan; Hinks, Jamie; Bazan, Guillermo C.
Abstract: Membrane‐intercalating conjugated oligoelectrolytes (COEs) are emerging as potential alternatives to conventional, yet increasingly ineffective, antibiotics. Three readily accessible COEs, belonging to an unreported series containing a stilbene core, namely D4, D6, and D8, were designed and synthesized so that the hydrophobicity increases with increasing side‐chain length. Decreased aqueous solubility correlates with increased uptake by E. coli . The minimum inhibitory concentration (MIC) of D8 is 4 μg mL −1 against both E. coli and E. faecalis, with an effective uptake of 72 %. In contrast, the MIC value of the shortest COE, D4, is 128 μg mL −1 owing to the low cellular uptake of 3 %. These findings demonstrate the application of rational design to generate efficacious antimicrobial COEs that have potential as low‐cost antimicrobial agents. Abstract : Three readily accessible conjugated oligoelectrolytes (COEs) were designed with a stilbene core but different molecular lengths to give varying solubility in aqueous solution. The latter correlates with cell affinity. The effective cellular uptake of the longest molecule leads to enhanced antimicrobial activity against Gram‐negative and Gram‐positive bacteria, demonstrating the potential of COEs as efficacious low‐cost antimicrobials.